The Geographic Spaces of ʿAjamī in West Africa - Barton, Karen S. (Islamic Africa, 2023)
The article highlights the geographical dimensions of African ʿAjamī traditions, with an emphasis on the Wolof, Fula, Mandinka, and Hausa traditions. It examines the spatial variation of these traditions, as well as their specific uses in different geographical spaces, places, and realms. The article shows how ʿAjamī documents – both historic and contemporary archives – are ubiquitous across Muslim West Africa and have been uncovered in both private and public spaces, playing an important role in everyday life. We explore how new cartographies that focus on the diffusion of ʿAjamī scripts and their broad reach can provide us with a richer understanding of African knowledge systems and their important footprint, helping to debunk stereotypes about African literacy.